The Outcomes of a Virtual Exchange (VE) Project Carried Out by Universities from Three Different Countries: Benefits of Collaborative Initiatives on Cultural Sensitivity Involving International Students at Universities - Horváth-Csikós, Gabriella (GILE Journal of Skills Development, 2024)
The VE project was implemented with the cooperation of three universities: Budapest Business University, University of Applied Sciences, Hungary; University of Sfax, Tunisia; and Izmir Democracy University, Turkey, in 2023. The main objective of the Virtual Exchange project was to provide students with opportunities for intercultural and interactional development through the performance of collaborative intercultural tasks. The further aim of the project was to provide students with international intercultural experience and to foster mutual understanding, global education, and digital literacy. We focused significantly on creating joint activities that encouraged international students to communicate in ways that enabled them to grasp knowledge beyond what they could merely acquire from websites or books. Both a preliminary survey and a follow-up survey were conducted among the students involved from the three universities, exploring their initial expectations and cultural perspectives before and after the project. The present study summarises the details and the experiences of the implementation of the Virtual Exchange Project, while another paper presents the results of the questionnaires in more detail.